An Adaptive Method for Reducing Vibrations of Circular Plates with Recursive Identification - Lucyna Leniowska; Marcin Grochowina; Mariusz Sierżęga; Bogumił Hołota (Applied Sciences, 2022)
The article presents an adaptive control procedure based on the online recursive identification of the best estimated model of plate bending vibration for vibration cancelation. The test object was a thin, circular aluminum plate, clamped at the edge, with MFC actuator and a velocity feedback signal. The sensor signal was collected using the non-contact laser measurement method. The system model of the plate was identified online using identification technique based on auto-regressive with exogenous input model. The control law was designed by the pole placement method solving the Diophantine equation. The adaptive controller we designed was implemented and tested on a real-time platform—PowerDAQ with an xPC Target environment. The results presented in the article confirm the correct operation of the adaptive controller and the reduction of vibrations in a fairly wide frequency band while maintaining a relatively low order of the system model.